2007
DOI: 10.1007/s11243-006-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, theoretical calculations and catalase-like activity of mixed ligand complexes derived from alanine and 2-acetylpyridine

Abstract: Mixed ligand complexes [M(2-AP)(Ala)Cl x AE mH 2 O]nH 2 O, where (M = Co II , Ni II , Cr III and Fe III , 2-AP = 2-acetylpyridine, Ala = alanine, x = 2-3, m = 0-1 and n = 3-5] are synthesized and characterized by elemental analysis, FTIR, UV/Vis., MS, TG, measurements and semi-empirical calculations ZINDO/1 and PM3. The results suggest an octahedral geometry for all isolated complexes. FTIR spectra show that alanine coordinates to the metal ions as a neutral unidentate through the amino nitrogen where 2-acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The binuclear Schiff base of glycine and 3-acetylpyridine were separated in the case of metal acetates where the pH (5) is suitable for condensation, while in the case of metal chlorides, the lower pH (2 to 4) blocks NH 2 as NH 3 + , glycine, and 3-acetylpyridine coordinate separately to the metal ion to form mixed ligand complexes. The same behavior was observed with the metal complexes of alanine and 2-acetylpyridine . In this work, we were able to separate the Schiff base complexes from the reaction of some metal chlorides with leucine and 2-acetylpyridine (although at the lower pH values 2 to 4).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The binuclear Schiff base of glycine and 3-acetylpyridine were separated in the case of metal acetates where the pH (5) is suitable for condensation, while in the case of metal chlorides, the lower pH (2 to 4) blocks NH 2 as NH 3 + , glycine, and 3-acetylpyridine coordinate separately to the metal ion to form mixed ligand complexes. The same behavior was observed with the metal complexes of alanine and 2-acetylpyridine . In this work, we were able to separate the Schiff base complexes from the reaction of some metal chlorides with leucine and 2-acetylpyridine (although at the lower pH values 2 to 4).…”
Section: Introductionsupporting
confidence: 73%
“…The same behavior was observed with the metal complexes of alanine and 2-acetylpyridine. 12 In this work, we were able to separate the Schiff base complexes from the reaction of some metal chlorides with leucine and 2-acetylpyridine (although at the lower pH values 2 to 4). This behavior is explained on the basis of electron-donating ability of the side chain of the amino acid which plays a role in achieving the condensation process between the amino group of leucine and the carbonyl group of 2-acetylpyridine by increasing the electron density on the amino nitrogen, hence increasing the ability of the nucleophilic attack from the amino nitrogen on the carbon atom of the carbonyl group.…”
Section: Introductionmentioning
confidence: 88%
“…The remaining of these bands unaltered, confirms the inertness of N-* N active sites towards coordination[20]. The presence of hydrated water in the Pt(II) complex is confirmed by the presence of bands at 3431, 746 and 690 cm -1 due to  (OH),  (OH) and  w (OH), respectively[27,28,29]. New weak bands are observed at 557 and 449 cm-1 due to ν (M-O), ν (M-N) respectively [20].…”
mentioning
confidence: 60%
“…N) and constant concentration of complexes (4.1 Â 10 À3 -8.2 Â 10 À3 mmol À1 ) at 25°C was studied ( Table 9). The conditions of catalytic decomposition reactions of hydrogen peroxide were chosen according to the similar studies in literatures [34,47]. The results showed that the decomposition percentage of hydrogen peroxide increased with time (Fig.…”
Section: Catalytic Activitymentioning
confidence: 99%